Analisis Kesulitan Belajar Siswa pada Mata Pelajaran Biologi Kelas X MAS Al-Ikhlas Karya Mukti - Asrina, Nur; Bialangi, Mursito S.; Mawaddah, Hayyatun; Buntu, Amalia; Rafiqah, Rafiqah; Agni, Raya (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the level of difficulty of students in the subject of biological diversity biology in class X of MAS Al-Ikhlas Karya Mukti and describe the factors that cause students' learning difficulties in the subject of biological diversity biology. This study uses a descriptive method with a qualitative approach. The subjects of this study consisted of 40 students in class X. The types and sources of data used are primary, namely the results of interviews and questionnaires, and secondary data in the form of curriculum documents such as Learning Implementation Plans (RPP). Data analysis is carried out by data reduction techniques, data presentation, and drawing conclusions. The results of the study showed that (1) the average level of student learning difficulty in biodiversity materials reached 65%, which was included in the high category. (2) Internal factors such as the physical and psychological condition of students (70%) in the high category, interest and motivation in learning (75%) in the high category, and cognitive ability (63%) in the medium category. (3) External factors such as the learning environment at school (69%) in the high category, family support (63%) in the medium category, peer influence (61%) in the medium learning difficulty category, and limited learning resources (54%) in the medium category. Thus, it can be concluded that the level of student learning difficulties in biodiversity materials in class X of MAS Al-Ikhlas Karya Mukti shows that students experience high learning difficulties influenced by a combination of internal and external factors.